Project-Based Learning as an Effective Pedagogical Intervention for Slow Learners in Elementary Science Education - Nasaruddin Nasaruddin; Mumpuniarti Mumpuniarti (Journal of Innovation and Research in Primary Education, 2026)
Slow learner students face significant challenges in science education due to cognitive processing difficulties and abstract concept comprehension limitations. This study investigated the effectiveness of Project-Based Learning (PjBL) in improving IPAS learning outcomes among slow learner students in elementary education. Employing Classroom Action Research following the Kemmis and McTaggart spiral model, the study was conducted across two iterative cycles with two sixth-grade slow learner students at SD Negeri 012 Sandaran during the 2024/2025 academic year. Data collection utilized mixed methods including pre-tests, post-tests, project assessment rubrics, structured observations, interviews, and documentation. Students engaged in hands-on environmental projects related to "Our Earth is Threatened," creating artwork from recycled materials while receiving intensive scaffolding and individualized support. Substantial learning gains were documented, with mean scores increasing from 35 (pre-test) to 62.5 (Cycle I post-test) and 82.5 (Cycle II post-test), representing a 135.7% improvement and successful achievement above the minimum mastery criterion (KKM = 75). Qualitative data revealed enhanced engagement, collaboration, motivation, and conceptual understanding. PjBL, when appropriately scaffolded and differentiated, constitutes an effective pedagogical intervention for slow learner students in elementary science education, aligning with constructivist learning principles and addressing their unique learning needs through concrete, authentic, and collaborative learning experiences.